Trade policies for a small open economy: The case of Singapore1. (11th September 2017) - Chen, Xiaoping; Shao, Yuchen
Abstract: This paper discusses the trade policies and practices of Singapore based on the latest WTO trade policy review. Though Singapore's trade policies have been effective and contributing to its remarkable economic performance, it also faces problems and new challenges in the modern globalisation era. Reviewing Singapore's policies also provides guidance for other small open economies.